A Syntactic Ambiguity Analysis of EFL Students’ Recount Text Using Syntactic Tree Diagrams - Riskawati Pakaya; Abid Abid; Sri Widyarti (Journal of English Language and Education, 2026)
This research aims to analyze the syntactic ambiguity in EFL students' recount texts by identifying the types and patterns of ambiguity and examining how differences in sentence structure can lead to various interpretations of meaning. A descriptive qualitative design was employed to identify results, with data consisting of ambiguous sentences taken from ten recount texts written by ten fourth-semester students in the English Language Education Program at Gorontalo State University. Data were collected through documentation. The results of the study showed that there are 16 sentences containing syntactic ambiguity. These ambiguities are classified into four types: noun phrase ambiguity, prepositional phrase ambiguity, adverbial ambiguity, and relative clause ambiguity, with 6 patterns of ambiguity occurring, such as (Adj+N+N), (Adj+N+conj+N), (VP+VP+AdvC), (V+NP+PP), (NP+NP+PP), and (NP+NP+RelC). The most dominant type found is prepositional phrase ambiguity. The analysis indicates that syntactic ambiguity arises because the grammatical arrangement of sentence elements allows for more than one possible structural interpretation. Furthermore, syntactic tree diagrams effectively reveal how differences between surface structure and deep structure produce multiple interpretations in students’ writing.